Bioactive-Loaded Hydrogels Based on Bacterial Nanocellulose, Chitosan, and Poloxamer for Rebalancing Vaginal Microbiota - Angela Moraru; Ștefan-Ovidiu Dima; Naomi Tritean; Elena-Iulia Oprița; Ana-Maria Prelipcean; Bogdan Trică; Anca Oancea; Ionuț Moraru; Diana Constantinescu-Aruxandei; Florin Oancea (Pharmaceuticals, 2023)
Biocompatible drug-delivery systems for soft tissue applications are of high interest for the medical and pharmaceutical fields. The subject of this research is the development of hydrogels loaded with bioactive compounds (inulin, thyme essential oil, hydro-glycero-alcoholic extract of Vitis vinifera, Opuntia ficus-indica powder, lactic acid, citric acid) in order to support the vaginal microbiota homeostasis. The nanofibrillar phyto-hydrogel systems developed using the biocompatible polymers chitosan (CS), never-dried bacterial nanocellulose (NDBNC), and Poloxamer 407 (PX) incorporated the water-soluble bioactive components in the NDBNC hydrophilic fraction and the hydrophobic components in the hydrophobic core of the PX fraction. Two NDBNC-PX hydrogels and one NDBNC-PX-CS hydrogel were structurally and physical-chemically characterized using Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and rheology. The hydrogels were also evaluated in terms of thermo-responsive properties, mucoadhesion, biocompatibility, and prebiotic and antimicrobial effects. The mucin binding efficiency of hydrogel base systems was determined by the periodic acid/Schiff base (PAS) assay. Biocompatibility of hydrogel systems was determined by the MTT test using mouse fibroblasts. The prebiotic activity was determined using the probiotic strains Limosilactobacillus reuteri and Lactiplantibacillus plantarum subsp. plantarum. Antimicrobial activity was also assessed using relevant microbial strains, respectively, E. coli and C. albicans. TEM evidenced PX micelles of around 20 nm on NDBNC nanofibrils. The FTIR and XRD analyses revealed that the binary hydrogels are dominated by PX signals, and that the ternary hydrogel is dominated by CS, with additional particular fingerprints for the biocompounds and the hydrogel interaction with mucin. Rheology evidenced the gel transition temperatures of 18–22 °C for the binary hydrogels with thixotropic behavior and, respectively, no gel transition, with rheopectic behavior for the ternary hydrogel. The adhesion energies of the binary and ternary hydrogels were evaluated to be around 1.2 J/m2 and 9.1 J/m2, respectively. The hydrogels exhibited a high degree of biocompatibility, with the potential to support cell proliferation and also to promote the growth of lactobacilli. The hydrogel systems also presented significant antimicrobial and antibiofilm activity.